Diversity and Abundance of Beetles on Cabbage Cultivation: Effects of Cultivation Methods and Landscape Composition - Marpaung, Leny Theresia Putri; Rizali, Akhmad (University of Brawijaya, 2025)
Cabbage (Brassica oleracea) is a vegetable crop with high commercial value in Indonesia. However, cabbage production still fails to meet consumer demand, with one of the causes being pest damage. Plant pest can be suppressed and controlled using natural enemies from various orders, including Coleoptera or beetles. Cultivation practices and landscape composition influence the presence of beetles. This study aims to investigate the characteristics of the landscape, the role of beetles, and the relationship between cultivation methods and landscape composition on the diversity, abundance, and composition of beetles. The research methods include determining the location and observation plots, mapping the landscape and characterizing the composition of the landscape, and setting traps for sampling, identification, and documentation. Data analysis used analysis of variance, analysis of similarity, and Generalized Linear Models (GLM). All data analyses were performed using RStudio software and the vegan package. Based on the research results, the dominant land use types are agriculture and natural habitats; beetles consist of predatory, herbivorous, decomposer, and scavenger beetles. Cultivation methods did not correlate with beetle diversity, abundance, and composition, whereas habitat conditions and landscape composition did correlate with beetle diversity, abundance, and composition.